2020
DOI: 10.1055/s-0040-1710555
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Immature Neutrophils in Preterm Infants with Feeding Intolerance

Abstract: Objective Feeding intolerance (FI) is a common presentation of necrotizing enterocolitis (NEC) and sepsis. NEC and sepsis are associated with hematological changes, but these changes alone are not reliable biomarkers for early diagnosis. This study examined whether the combination of hematological indices and FI can be used as an early diagnostic tool for NEC or sepsis. Study Design This retrospective cohort study included infants born at <1,500 g or <30 weeks who had symptoms of FI. The excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…16 Feeding intolerance is often associated with NEC and sepsis and with hematological changes, such as a decrease in platelet count and an increase in the ratio of immature neutrophils to total neutrophils (I/T ratio). 17 The gut microbiome has also been implicated in feeding intolerance, with differences in gut flora composition observed between infants with feeding intolerance and those with feeding tolerance. 18 Several studies have reported that preterm infants with food intolerance have a longer hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…16 Feeding intolerance is often associated with NEC and sepsis and with hematological changes, such as a decrease in platelet count and an increase in the ratio of immature neutrophils to total neutrophils (I/T ratio). 17 The gut microbiome has also been implicated in feeding intolerance, with differences in gut flora composition observed between infants with feeding intolerance and those with feeding tolerance. 18 Several studies have reported that preterm infants with food intolerance have a longer hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Intolerance occurs because the functions of various organs have not fully developed in newborn infants, who cannot digest food in a timely manner after feeding. In general, the best food for newborn infants is breast milk, but feeding intolerance often occurs when some parturients cannot provide breast milk for some reasons such as breast milk insufficiency or suffering from infectious diseases [ 18 – 21 ]. In addition, compared with the fetuses delivered at term, premature infants have more incomplete development of various functions and a larger incidence of feeding intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in some cases, mental retardation also affects premature infants, further increasing the probability of death. erefore, the academic community should pay more attention to further exploring the clinical symptoms of premature infants with FI to provide solid theoretical support for the selection of suitable treatment and drugs [4][5][6][7]. At present, erythromycin is the main drug for the treatment of FI in clinical practice, whose mechanism is to enhance gastrointestinal motility and subsequently relieve the symptoms of FI in affected infants; however, this drug can also increase the incidence of abdominal pain and abdominal distension, so combination therapy should be implemented to improve treatment effect of FI.…”
Section: Introductionmentioning
confidence: 99%